4.A. Workshop: Developing a European planetary health curriculum model. Can we adapt Ireland's approach?. (20th October 2021) - ,; ,
Abstract:  : The climate crisis is reaching an irreversible tipping point. If the planet continues on its current trajectory of rising global temperatures and increasing ecological instability, then humans will be faced with catastrophic environmental and health effects. In acknowledgement of the interface between environmental change and human health, there is an increasing international mandate to integrate themes of sustainability, climate change and ecological instability into the health professional curriculum. As a result, planetary health is a growing field in health and medicine, but despite this, those working in the field are facing a number of challenges to its implementation that need to be overcome. The aim of this workshop is to explore examples of planetary health curricula development and to examine how best to implement such curricula for undergraduate health professionals across Europe. The workshop will open with a brief overview of the concept of planetary heath and the role of the health professional in responding to the climate crisis, summarising the current evidence in the field, before participating panellists each present the work they are undertaking in their own universities to develop planetary health curricula for undergraduate health professionals. Firstly they will briefly describe material covered in the curriculum before identifying any barriers and facilitators to implementation they have encountered. The panel discussion will then focus on the potential to develop shared undergraduate curricula in planetary health across European countries. To conclude there will be an opportunity for the audience to participate in Q and A. Participating panel members include Dr Sofia Hammarstrand, Occupational and Environmental Medicine, Sahlgrenska University Hospital and Gothenburg University, Sweden, Dr Debbi Stanistreet, RCSI University of Medicine and Health Sciences, Dr Heather Baid, The University of Brighton, and Dr Peter Blankestijn, The University Medical Centre Utrecht. Speakers/Panelists: Deborah Stanistreet Royal College of Surgeons in Ireland, Dublin, Ireland Peter Blankestijn University Medical Centre Utrecht, Utrecht, Netherlands Heather Baid University of Brighton, Brighton, UK Key messages: Participants will become familiar with examples of planetary health curricula for student health professionals. Participants will be able to identify challenges to implementing planetary health curricula and opportunities for an integrated approach across Europe.